Comportamento dos preços de terras em região de fronteira agrícola e em áreas tradicionais - Ferro, Aline Barrozo (Universidade Federal de São Carlos, 2012)
This study aims to evaluate the impact of some factors on prices of agricultural land in three different regions: agricultural frontier (in the south of Maranhão, south of Piauí, eastern region of Tocantins and west of Bahia), transition area (relatively recent agricultural use of the land; however, it already represents a major soybean producing region, such as the Central-Western region in Brazil) and developed (more traditional agricultural areas, such as the South of Brazil). The period of the analysis is from 2002 to 2010, due to the recent availability of prices of regional lands. Several studies regarding the land market were analyzed; consequently, some factors related to the revenue obtained with land, to the technological level, to the infrastructure, to the need of credit, to the availability of land to expand crops and to one factor linked to expectations of agents. The elasticity in relation to the land price was obtained, using the econometric model of panel data. Soybean prices, which represent the revenue of land, had a positive relation with the price of this factor. Moreover, it was possible to verify that, in less occupied regions, an increase in the demand for area may bring negative impacts on its prices, because of the higher elasticity of the land supply and the possibility to convert raw lands and pastures in agricultural areas. This occurs because the land conversion shifts the supply curve to the right, which might impact negatively the land price. On the other hand, in the developed area, the relation is positive, since the land supply is almost inelastic. The factor of speculation was very important in the agricultural frontier region, differently from what was observed in other regions, which has highlighted the sharp interest of investors groups interested in the potential of the land valuation in that region in the period considered.
Keywords: dados em painel; mercado de terras; fronteiras agrícolas; land market; agricultural frontier; panel data; CIENCIAS SOCIAIS APLICADAS::ECONOMIA